Candidemia associated with COVID-19: risk factors and predisposition in critical patients - Monteiro da Silva Rodrigues Coutinho, Natália; da Rosa Monte Machado, Gabriella; Ferreira do Amaral, Thaís; Lettieri Teixeira, Mário; Meneghello Fuentefria, Alexandre (Clinical and Biomedical Research, 2024)
Introduction: Coronavirus diasease 19 (COVID-19) is an infection caused by the new coronavirus - SARS-CoV-2 in 2019. The infection quickly spread throughout the world, establishing itself like a pandemic. Reports on secondary fungal co-infections in critically ill patients COVID-19 are still scarce and their dynamics are poorly understood. Candidemia is defined as the presence of Candida species in one or more blood cultures, being one of the most reported opportunistic fungal infections in intensive care units (ICU). Methods: Three databases were used for the literary search: Pubmed, Science Direct, and Scopus, including articles published between 2020 and 2021. Results: The incidence of candidemia in COVID-19 patients ranged up to 12% of COVID-19 reported cases. Candida albicans was the most prevalent species, followed by non-albicans species. The use of broad-spectrum antimicrobials, corticosteroids, central venous catheters, mechanical ventilation, parenteral nutrition, immunosuppressants such as tocilizumab and prolonged hospital stay were predisposing factors for the candidemia in COVID-19 patients. Conclusion: There are strongly established risk factors that influence the establishment of candidemia in critically ill COVID-19 patients, which contributes to increased mortality in these patients. Finally, active surveillance by the medical team should be maintained for previous signs of fungal co-infection associated with SARS-CoV-2 contamination.